Daily Bread: Women's Self-Help Microfinance and the Social Meanings of Money. (June 2023) - Bott, Esther; Ojha, Shalini; Mini, Sunita; Kamal Kumar, Rajeev; Choudhary, Sunil; Yaron, Gil; Smyth, Alan R
In this article, we explore the impacts and implications of 'Rojiroti', a women's self-help group (SHG) microfinance scheme operating in poor communities in Bihar, India. We focus particularly on how improvements found in women's circumstances and in children's health might result from Rojiroti SHG membership. Through data from 5 focus groups and 19 individual interviews with women in communities where Rojiroti operates, we discover how the scheme is regarded and how it affects women's management of household budgets. Moreover, we explore the relational aspects of SHG microfinance and the ways that it can alter family and social dynamics. Drawing on notions of 'earmarked' money and 'safeguarded' money, we argue that the money itself has meaning and non-pecuniary value in the form of other currencies, including power and agency, which can lead to the improved well-being and health of families.